Isotopic record of Pleistocene glacial/interglacial cycles in pelagic carbonates: Revisiting historical data from the Caribbean Sea - Hermoso, M (Elsevier, 2016)
The glacial/interglacial cycles of the Pleistocene were first recognised by variations in the oxygen isotopic composition of planktonic foraminifera from cores in the Caribbean Sea. Since this pioneering work by Emiliani, this proxy has been extensively applied to a variety of carbonate biominerals over the entirety of the Meso-Cenozoic. However, palaeoceanographic studies have overwhelmingly focused on foraminifera compared to other calcifying microorganism fossils, such as the coccoliths. In this study, I revisit coccolith stable isotopic data obtained from the classic P6304-4 core in light of recent developments in the biogeochemistry of coccolithophores. In particular, I show that the coccolith stable isotope record of the last 13 Marine Isotope Stages (∼480 kyrs) is significantly biased by large vital effects. The magnitude of coccolith carbon and oxygen isotope vital effects is not uniform, but shows remarkable co-variance with the Vostok CO2 ice record. During periods of relatively elevated CO2 (interstadials), the expression of the vital effect is relatively small, whereas it can as high as +3‰ for the oxygen isotopes during glacial stadials, which I argue is a result of enhanced CO2 limitation of coccolithophores. Using this paradigm, I propose that coccolithophore vital effects are not a complicating factor, but rather the signal of interest. As the magnitude of the coccolith vital effect is shown to scale with pCO2, coccolith carbon and oxygen isotopes may be used in conjunction with foraminifera data to reconstruct and refine aqueous CO2 concentrations in the past.